2022
DOI: 10.3897/popecon.6.e90723
|View full text |Cite
|
Sign up to set email alerts
|

From intention to action: factors of vaccine hesitancy and vaccine refusal during the COVID-19 pandemic

Abstract: According to results of the vaccination campaign against COVID-19, Russia has failed to reach indicators of the developed countries on vaccination coverage and is sustainably below the global average. The purpose of this article is to identify and quantify factors of vaccine hesitancy and vaccine refusal in Russia during the following periods: prior to mass vaccination campaign and upon completion of its most active phase. We use data from the two surveys conducted in January-February and November-December, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…In contrast, being above the age of 80 was associated with a decrease in the odds of hesitancy. This may be due to the fact that the elderly population, who are at the greatest risk of adverse Covid-19 disease outcomes [ 14 , 15 ], were intentionally targeted for vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, being above the age of 80 was associated with a decrease in the odds of hesitancy. This may be due to the fact that the elderly population, who are at the greatest risk of adverse Covid-19 disease outcomes [ 14 , 15 ], were intentionally targeted for vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…population, who are at the greatest risk of adverse Covid-19 disease outcomes [14,15], were intentionally targeted for vaccination. We also found that education was significantly associated with vaccine uptake, with those with secondary or post-secondary education more likely to be classified as acceptors with doubts.…”
Section: Plos Global Public Healthmentioning
confidence: 99%